Influence of Intrinsic Myocardial Conduction on Paced QRS Morphology During Cardiac Resynchronization Therapy Follow up - Deshmukh, Rajendra (Indian Heart Rhythm Society, 2008)
We report two cases of patients of cardiac resynchronization therapy (CRT) whose ECGs, during follow up, showed different paced QRS morphology as compared to those of immediate post-device implantation. Parameters of leads, including sensitivity and capture thresholds, were unchanged. There was no lead dislodgement confirmed on fluoroscopy. The ECGs obtained in device off mode showed different intrinsic QRS morphology as compared to those of pre-implant morphology. These changes were attributable to electrolyte imbalance in one patient and progressive intraventricular conduction defect in the other. These cases demonstrate that intrinsic myocardial conduction pattern influences paced QRS morphology. Irreversible change in paced QRS morphology may indicate poor prognosis.